Investigation on pilot injection with low temperature combustion of Calophyllum inophyllum biodiesel fuel in common rail direct injection diesel engine. (15th December 2019) - Susanth Kishna, R.; Nanthagopal, K.; Ashok, B.; Srinath, R.; Pranava Kumar, M.; Bhowmick, Pathikrit
Graphical abstract: Highlights: B20 blend of Calophyllum inophyllum is fuelled in common rail direct injection engine. Pilot fuel and exhaust gas recirculation is varied at different operating conditions. Variation in pilot fuel increases the efficiency as close to diesel fuel. Increased pressure and heat release rate is exhibited for variation in injection strategies. NOx emissions is reduced by the addition of EGR. Abstract: The present research work emphasises on the utilization of Calophyllum inophyllum biodiesel and preparation of 20% blend sample to explore the effects of variation of multiple injection strategies and amount of exhaust gas recirculation in a common-rail direct injection engine. In this aspects, the pilot injection quantity of B20 blend has been varied from 5 to 15% for the improvement of diesel engine characteristics. Among the tested results, an optimum pilot injection quantity has been identified and the same experimental work is extended for the addition of 10% and 20% exhaust gas recirculation under same operating conditions. The experimental study revealed that the increase in pilot injection rate from 5% to 15% at same operating conditions has shown higher brake thermal efficiency of 36.8% and the same improvement has not observed during exhaust gas recirculation addition. In terms of emissions point of view, the 15% pilot injection quantity of B20 fuel has resulted lowest hydrocarbon and carbon monoxide emissions when compared to diesel fuel by about 54.4% and 45.9% respectively. However, the implementation of 10% EGR rate at 15% pilot injection quantity reduced the oxides of nitrogen emission by 10.04%. On the other hand, the combustion characteristics are enhanced during increase in pilot injection rate and it decreased to lower level at higher concentration of EGR addition. Thus, the combined effect of 15% pilot injection rate and 10% EGR rate would be a best possible option for obtaining an improved performance and emission characteristics. Further, the study can be extended to vary the pilot injection, main and post injection timings with suitable EGR addition successful running of biodiesel blend.